Groundwater Quality and Suitability Assessment in Tirupur Region, Tamil Nadu, India - Kumar G.; Saravanan Kothandaraman; Kathiresan Karuppanan; Sajjad Hussain (Journal of Chemistry)
The study aims to understand the hydrochemical characteristics and groundwater suitability for agricultural and drinking purposes. For this purpose, 21 groundwater samples were collected, and major physicochemical parameters such as pH, EC, TDS, temp, salinity, Ca2+, Mg2+, Na+, K+, HCO3−, Cl−, and SO42− were analyzed, followed by the standard analytical procedures. Different groundwater quality graphical representations were constructed by using Aqua Chem software. The results indicate groundwater samples were alkaline with fresh to moderate saline in nature, sixty-eight percent of the samples were suitable for drinking in accordance with WHO, and thirty-two percent of the samples were unsuitable due to the excess amount of different ionic concentrations derived from natural and various anthropogenic sources. Irrigation water quality parameters such as SAR, EC, PI, Na %, RSBC, MR, and KR were used to understand the irrigation suitability. The US salinity diagram exemplifies that most groundwater samples fall in the C3S1 category with high salinity hazard and low alkali hazard. The Wilcox plot reveals that 80% of the samples were found under very good to permissible limits, and few samples fall with doubtful to unsuitable quality due to the excess amount of alkali and salinity. Permeability index values show that groundwater is suitable for irrigation. Three major hydrochemical facies were identified with the dominance order of mixed CaMgCl, NaCl, and CaCl. Gibb’s plot suggests that evaporation and rock-water interaction are the dominant natural mechanisms controlling the groundwater chemistry in the present study area.